Which is worse; divorce or conflict? parental divorce, interparental conflict, and its impact on romantic relationship quality of young dating adults in the Maldives - Shanoora, Aishath; Hamsan, Hanina H.; Abdullah, Haslinda; Mohd. Khir, Azlina (Human Resource Management Academic Research Society, 2020)
Past research has documented the negative impact of parental divorce and interparental conflict on romantic relationship quality but in isolated studies. Limited studies have compared both parental divorce and interparental conflict on young adult’s dating relationships. This study aimed to fill this gap by identifying the roles of parental divorce and interparental conflict and how they interact on the relationship between parental divorce, interparental conflict, and romantic relationship quality of young adults. A total of 297 Maldivian undergraduate students, who were in a dating romantic relationship, between the ages of 18 to 25 participated in the study. Data was collected using a self-administered set of questionnaires. Relationship quality was measured using the Relationship Quality Component Inventory and perceived interparental conflict was measured using Children’s Perception of Interparental Conflict Scale (CPIC). The collected data were analyzed using IBM Statistical Package for Social Sciences (SPSS) and PLS-SEM software. Results revealed that parental divorce and interparental conflict was negatively associated with low romantic relationship quality. Additionally, Perceived interparental conflict mediated the relationship between parental divorce and relationship quality of young dating adults.